A Study of Sound Materials of Water Hyacinth (Eichhornia Crassipes) as Alternative STEAM Integrated Project-Based Learning Model (PjBL) - M. Hidayatur Rohman; Putut Marwoto; Sigit Priatmoko (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This study aims to find an alternative sound-absorbing material from nature that is cheap and environmentally friendly, namely the water hyacinth plant (Eichhornia crassipes). The experimental soundproofing tool from a glass box with a placemat skat was developed by integrating science, technology, engineering, arts, and mathematics (STEAM) elements as an alternative project-based learning model (PjBL) for students. The research method used is experimental. Water hyacinth was sun-dried, woven in the form of a placemat with two variations of the test samples at several frequencies of 250 Hz, 500 Hz, 750 Hz, 1000 Hz, and 1500 Hz. Six stages of PjBL are used, and elements of STEAM are integrated. The results of the study obtained the value of Noise Reduction (NR) of sound for test samples 1, test sample 2, or a combination of test samples 1 and 2. Each test sample is effective at 1500 Hz high frequency; namely, test NR 1 = 8.7 dB, test NR 2 = 8.3 dB, and NR Gab=9.3 dB. The combined test sample was also effective at frequencies of 500 Hz and 750 Hz, with NR Gab=4.3 dB and NR Gab=4.7 dB. Following the theory that changes in sound between 3 to 12 dB have effects that humans can feel. This study concludes that natural water hyacinth fiber has fairly good quality as an alternative sound-dampening material. This experimental tool can also be an alternative to the STEAM-integrated PjBL learning model.